The Effect of Hearing Aids and Cochlear Implants on Balance During Gait. Issue 9 (October 2017) - Weaver, Tyler S.; Shayman, Corey S.; Hullar, Timothy E.
Abstract : Hypothesis: Auditory input in people with hearing impairment will improve balance while walking. Background: Auditory input is increasingly recognized as an additional input for balance. Several studies have found auditory cues to improve static balance measured on a sway platform. The effect of audition on gait, a dynamic task also linked to fall risk, has not been fully examined. If a positive effect were shown between audition and balance, it would further indicate that improving hearing could also improve balance. Methods: Inertial sensors quantified gait parameters of 13 bilateral hearing aid users and 12 bilateral cochlear implant (CI) users with their hearing devices on and off. Outcome measures included gait velocity, stride length variability, swing time variability, and double support phase. Results: Group analysis of each of the gait outcomes showed no significant differences between the aided and unaided conditions in both the hearing aid and CI groups. Gait velocity, an outcome most strongly linked to fall risk had 95% confidence interval differences of −2.16 to 1.52 and −1.45 to 4.17 cm/s in hearing aid and CI users, respectively (aided versus unaided condition). There was considerable variation among participants with some individuals improving in all four parameters. Conclusion: The overall findings were not statistically significant, however, a small subset of our population improved clinically across several outcomes. This demonstrates that audition may have a clinically beneficial effect on balance in some patients.